Intersectoral Competition for Water Between Users and Uses in Tamil Nadu-India - Suresh, S. (Frontiers in Earth Science, 2021)
Water is a manageable asset for drinking, food creation, and industry, and demand increases as the population increases. Water for irrigated agriculture, industry and domestic needs in India will go up to 1,072, 130, and 102 billion m3 (BCM) by the year 2050. In the state of Tamil Nadu in 2025, water needs for irrigation, domestic, livestock, and industrial sectors will be 52.7, 1.5, 1, and 2 billion m3, respectively, against the available supply of 24.6 BCM of surface water and 23 BCM of groundwater during the same period. A balance between need and supply is often difficult to achieve. By the year 2050, some 60 per cent of the world’s population will live in cities. In India and Tamil Nadu, 38 and 48 per cent of people will live in cities. Tamil Nadu is the second most urbanized state in India with 48 per cent of its population living in cities. This urban push will demand a large share of common water resources and most of the reservoir systems will face increased water demand for non-agricultural purposes, bringing in imbalances with other sectors, namely agriculture. Contrary to mounting demand, it will be difficult to facilitate the growing need for water. Furthermore, there are social and environmental costs in terms of the diversion of water from agriculture to urban uses. The discharge of sewage and industrial effluents also pollutes surface and groundwater, affecting not only human health but also the entire ecosystem. This paper examines the water management challenges in Tamil Nadu, India with respect to meeting future water demands across competing sectors.